Study on the evolution of the spatial structure and driving force of traditional village tourism in South Anhui province - Zhang, Le; Zhou, Siyi; Guo, Yanlong (Frontiers in Earth Science, 2024)
The development of the tourism industry is a crucial mechanism for enhancing the tertiary sector and promoting local economic growth. This study focuses on traditional villages in the southern Anhui region, analyzing the characteristics of the evolution of their tourism spatial structure and the underlying driving forces. The objective is to provide foundational insights for rural tourism and policy development in the region. Utilizing ArcMap 10.8, we assess the evolution of the tourism spatial structure through the selection of 14 indicators across three dimensions: resource endowment conditions, the regional tourism development environment, and the local economic construction environment, thereby establishing an evaluation system. The Entropy Weight-TOPSIS method is employed for comprehensive data analysis. The findings indicate: 1) The development status of tourism in traditional villages is gradually declining, significantly impacted by the pandemic; 2) Among the six cities in southern Anhui, Huangshan and Wuhu exhibit relatively favorable development conditions, while Ma'anshan and Xuancheng are at moderate levels. Chizhou and Tongling are facing weaker development states; 3) Regional investment, commercial value, and ecological environmental protection capabilities are the three primary driving factors influencing the evolution of tourism spatial structure in southern Anhui, followed by environmental quality and cultural heritage preservation. Therefore, policymakers should place greater emphasis on boosting tourism development in Chizhou and Tongling, enhancing regional investment levels, and improving the commercial value and ecological protection capabilities of tourism spaces. Furthermore, attention must be devoted to environmental quality and cultural heritage preservation within the rural tourism landscape of southern Anhui to ensure sustainable development.